Effect of rapid maxillary expansion on the dimension of the nasal cavity and on facial morphology assessed by acoustic rhinometry and rhinomanometry Efeito da expansão rápida da maxila na dimensão da cavidade nasal e morfologia facial pela rinometria acústica e rinomanometria - Carla Enoki Itikawa; Fabiana Cardoso Pereira Valera; Mírian Aiko Nakane Matsumoto; Wilma Terezinha Anselmo Lima (Dental Press Editora, 2012)
OBJECTIVE: To assess the effects of rapid maxillary expansion on facial morphology and on nasal cavity dimensions of mouth breathing children by acoustic rhinometry and computed rhinomanometry. METHODS: Cohort; 29 mouth breathing children with posterior crossbite were evaluated. Orthodontic and otorhinolaryngologic documentation were performed at three different times, i.e., before expansion, immediately after and 90 days following expansion. RESULTS: The expansion was accompanied by an increase of the maxillary and nasal bone transversal width. However, there were no significant differences in relation to mucosal area of the nose. Acoustic rhinometry showed no difference in the minimal cross-sectional area at the level of the valve and inferior turbinate between the periods analyzed, although rhinomanometry showed a statistically significant reduction in nasal resistance right after expansion, but were similar to pre-treatment values 90 days after expansion. CONCLUSION: The maxillary expansion increased the maxilla and nasal bony area, but was inefficient to increase the nasal mucosal area, and may lessen the nasal resistance, although there was no difference in nasal geometry. Significance: Nasal bony expansion is followed by a mucosal compensation. OBJETIVO: avaliar o efeito da expansão rápida da maxila na dimensão da cavidade nasal e na morfologia facial através da rinometria acústica e rinomanometria computadorizada. MÉTODOS: foram avaliadas 29 crianças na fase de dentição mista, portadoras de respiração bucal e mordida cruzada posterior. A documentação ortodôntica e a avaliação otorrinolaringológica foram realizadas em três tempos - antes da expansão rápida da maxila, imediatamente após e 90 dias depois. RESULTADOS: a expansão promoveu um aumento na dimensão da cavidade nasal e na maxila transversalmente. Contudo, não houve diferenças significativas na área da mucosa nasal. A rinometria acústica mostrou que não houve diferenças na área de secção transversa ao nível da válvula e concha nasal inferior; entretanto, a rinomanometria mostrou diferenças estatisticamente significativas na resistência nasal, que diminuiu após a expansão rápida da maxila. CONCLUSÕES: a expansão maxilar aumenta a área óssea maxilar e nasal; contudo, esse aumento não foi suficiente para aumentar a área da mucosa e diminuir a resistência nasal. Importância: a expansão óssea nasal foi seguida por uma compensação da mucosa.